Exosomal Circular RNA RNA-seq Profiling and the Carcinogenic Role of Exosomal circ-CYP24A1 in Cutaneous Squamous Cell Carcinoma - Zhang, Zheng; Guo, Hao; Yang, Wenjia; Li, Jiuhong (Frontiers in Medicine, 2021)
Objective: Aberrantly expressed exosomal circular RNAs (circRNAs) have been reported in various human cancers. Nevertheless, it remains elusive in cutaneous squamous cell carcinoma (cSCC). Herein, based on RNA-seq, we systematically uncovered the expression and implication of exosomal circRNAs in cSCC. Methods: Plasma exosomes derived from cSCC and healthy subjects were characterized by nanoparticle tracking analysis (NTA), transmission electron microscopy (TEM) and western blot. Differentially expressed exosomal circular RNAs (circRNAs) were screened by RNA-seq analysis, which were validated by RT-qPCR. Among them, the biological structure of circ-CYP24A1 was validated by Sanger sequencing and RNase R digestion. Si-circ-CYP24A1 was transfected into exosomes, followed by incubation with A431 and SCL-1 cells. Then, viability, apoptosis, migration, and invasion were evaluated by CCK-8, TUNEL staining and migration assays. Results: This study identified 25 up- and 76 down-regulated exosomal circRNAs in cSCC than healthy subjects. Among them, circulating circ-CYP24A1 was confirmed to be up-regulated in cSCC. Circ-CYP24A1 had a covalently closed circular structure and was not sensitive to RNase R digestion. After incubation with si-circ-CYP24A1-transfected exosomes, proliferation, migration, and invasion were lowered while apoptosis was enhanced in A431 and SCL-1 cells. Meanwhile, si-circ-CYP24A1-transfected exosomes significantly decreased the expression of downstream targets CDS2, MAVS and SOGA in cSCC cells. Conclusion: Collectively, our study identified that targeting exosomal circ-CYP24A1 could suppress cSCC progression by weakening tumor malignant behaviors, which might provide a promising therapeutic target and noninvasive diagnostic biomarker for cSCC.